Advanced Web Services - Bouguettaya, Athman; Sheng, Quan Z.; Daniel, Florian; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Web services and Service-Oriented Computing (SOC) have become thriving areas of academic research, joint university/industry research projects, and novel IT products on the market. SOC is the computing paradigm that uses Web services as building blocks for the engineering of composite, distributed applications out of the reusable application logic encapsulated by Web services. Web services could be considered the best-known and most standardized technology in use today for distributed computing over the Internet. This book is the second installment of a two-book collection covering the state-of-the-art of both theoretical and practical aspects of Web services and SOC research and deployments. Advanced Web Services specifically focuses on advanced topics of Web services and SOC and covers topics including Web services transactions, security and trust, Web service management, real-world case studies, and novel perspectives and future directions. The editors present foundational topics in the first book of the collection, Web Services Foundations (Springer, 2013). Together, both books comprise approximately 1400 pages and are the result of an enormous community effort that involved more than 100 authors, comprising the world$1 (Bs leading experts in this field.s
Design and Management of Web Service Transactions with Forward Recovery -- A Generic Framework for Testing the Web Services Transaction -- Universal Identity Management Based on Delegation in SOA -- The Roadmap of Trust and Trust Evaluation in Web Applications and Web Services -- Web Service-based Trust Management in Cloud Environments -- Web Service Contracts: Specification and Matchmaking -- A Certification-Aware Service-Oriented Architecture -- A Test Automation Framework for Collaborative Testing of Web Service Dynamic Compositions -- WSDARWIN: Studying the Evolution of Web Service Systems -- SCML: A Change Management Language for Adaptive Long Term Composed Services -- A Semantic-based Approach to Generate Abstract Services for Service Organization -- Exploring Service Networks of Biological Processes on the Web -- Automating Tendering Processes with Web Services: A Case Study on Building Construction Tendering in Hong Kong -- Service Trust Management for E-Government Applications -- Trust-Oriented Service Provider Selection in Complex OnlineSocial Networks -- AnalyzingWeb Services Networks: Theory and Practice -- Work as a Service -- Virtualizing Software and Human for Elastic Hybrid Services -- Realizing a Social Ecosystem of Web Services -- ubiREST: A RESTful Service-oriented Middleware for Ubiquitous Networking -- MobileWeb and Cloud Services -- TOSCA: Portable Automated Deployment and Management of Cloud Applications -- A V-Model Approach for Business Process Requirements Elicitation in Cloud Design -- Cloud-based Systems Need Multi-level Management -- Web Services for Things.
Keywords: Computer science; Computer Communication Networks; Database management; Information storage and retrieval systems; Computer Science; Information Systems Applications (incl. Internet).; Database Management; Information Storage and Retrieval; Computer Communication Networks; Computer Applications